Movimentos dos íons nitrato e amônio em colunas de material de solos do Triângulo Mineiro e de Pirapora - A A Guedes, Geraldo; Moura Filho, Waldemar; A Nogueira Fontes, Luiz (Revista Ceres, 2025)
The movement of nitrate and ammonium nitrogen through columns of soil materials was studied. Samples of a Dark Red Latosol from two slope positions at Capinópolis and of a Red-Yellow Latosol from Pirapora, both iocalities in Minas Gerais State, Brazil, were used.